PENDIDIKAN AL-QUR’AN DALAM TINJAUAN KITAB AL-WAJIZ FI ‘ILMI AL-QUR’AN AL-‘AZIZ KARYA KIAI SOLEH DARAT AL-SAMARANI - M. Izzad Khairi Yazdi; Agus Pahrudin; Ali Murtadho; Achi Rinaldii (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Al-Mursyid al-Wajiz fi Ilm al-Quran al-Aziz, a novel by Kiai Saleh Darat al-Samari, is a thorough examination of the ulumul Koran (sciences of the Koran) that is ideal for beginners. This study combines a historical-philosophical perspective with qualitative library research techniques to investigate the benefits of studying the Al-Quran via its historical legacy. The primary source for this study is the writings of Kiai Saleh Darat. Data is examined using content analysis. 1) This novel's Al-Quran learning module, which focuses on the core ideas and codification of the Al-Quran, followed by Al-Quran madrasah and recitation; 2) The criteria for an Al-Qur’an educator according to Kiai Saleh Darat include: a)Islam, which is logical, old, tsiqah, and memorized; b) Having an unbroken chain of authorities; c) Possess religious knowledge; d) May be paid, but this is not the primary objective; e) Ethical. According to the Al-Quran, students must: a) seek knowledge for Allah's sake; b) select teachers with high moral standards; c) behave well; d) act seriously, love friends, and remain steadfast; e) possess high moral standards; and f) put their knowledge of the Al-Quran into practice by practicing talaqqi and musafahah.